The Effect of Environmental Performance, Corporate Social Responsibility, Earnings Per Share, and Return on Assets on Stock Returns on Manufacturing Companies - Jeremy Harimauwan; Hendro Lukman (Graduate Program of Universitas Tarumanagara, 2023)
Every financial information disclosed by a company in the financial statements or annual reports will determine the response of investors in conducting stock investment activities. Public companies tend to require additional funds from external parties such as investors in order to finance their operations. To attract the attention of investors, a company must produce financial performance such as the level of company profitability which can provide significant benefits to investors. In addition, the environmental activities disclosed by the company can also provide input to investors if they want to invest in the company. This study aims to determine how Environmental Performance, Corporate Social Responsibility, Earning Per Share, and Return on Assets have an impact on the level of Stock Return of manufacturing companies listed on the BEI. The results obtained in this study show that the Environmental Performance variable has no effect on Stock Return, Corporate Social Responsibility has a negative effect on Stock Return, and Earning Per Share and Return on Assets have a positive effect on Stock Return. The implication of this research is that investors pay attention to business sustainability, the company must present an Environmental Performance that is more attractive to investors.